(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aims to identify the clinical and functional anorectal characteristics of children with refractory constipation using anorectal manometry and to assess symptom improvement potential based on functional anorectal profiles. Method: A cross-sectional study was conducted on 45 pediatric patients with refractory constipation symptoms, using parental retrospective interviews and data reviews, at the Anorectal Manometry Unit, Children’s Hospital 2, Ho Chi Minh City. Results: Fecal incontinence was present in 47.8% of pediatric patients with constipation symptoms. Following intensive therapy, 65.2% exhibited symptomatic improvement. The study revealed significant differences in resting anal pressure and cough pressure among fecal incontinence status groups. Conclusion: Our study results suggest that the primary mechanism of refractory constipation is functional outlet obstruction disorder. Anorectal manometry proves valuable in explaining the pathophysiology of fecal incontinence in children with refractory constipation.